The Hitler Years, Volume 2: Disaster 1940-1945 - McDonough, Frank 1957- (Head of Zeus, 2020)
A new narrative of the rise and catastrophic fall of the Nazi regime: a twelve-year descent into barbarism, genocide and aggressive war that cost over 50 million lives.